HIGH DEGREE OF CATIONIC ORDERING IN THE STRUCTURE OF A NEW MINERAL OF THE LABUNTSOVITE GROUP - Zolotarev Jr.A.A.; Krivovichev S.V.; Yakovenchuk V.N.; Pakhomovsky Ya.A.; Organova N.I.; Armbruster T. (My University, 2006)
In recent years, minerals of the labuntsovite group (hereafter, LG) have become objects of many detailed mineralogical and crystallochemical studies stimulated by numerous findings of these minerals and the diversity of their chemical compositions and physicochemical properties. The LG minerals also attract interest owing to the possibility of their application in catalytic processes, adsorption, and ion exchange.
Keywords: labuntsovite group minerals